The use of cutometer to evaluate the skin elasticity on the face (Journal of Face Aesthetics, 2022)
This paper presents the possibilities of pre‑treatment instrumental diagnosis assessing the condition of various facial skin areas. Tests which are aimed at determining the elasticity of facial skin were conducted. Analysis of skin parameters in selected facial areas in adults over a wide age range was performed using the Cutometer Dual MPA 580 probe. Parameters R2, R5, R7 were analysed. The following results were obtained: R2 (0.66–0.82) a.u.; R5 (0.60–0.92) a.u.; R7 (0.37–0.52) a.u. On the basis of the other parameters it can be concluded that skin elasticity and an ability to return to its original shape around the eyes, on the cheeks and around the lips is greater in younger patients than in older groups. There were no statistically significant differences within each age group between the right and left sides of the face. The ageing process simultaneously affects the entire facial skin which was confirmed by skin elasticity testing.
Keywords: cutometer; face; skin diagnostics; mechanical skin parameters